Otonomi Daerah, Kebijakan Publik, dan Penguatan Demokrasi Lokal di Kabupaten Lamongan - Moh Sa’diyin; Sutopo Sutopo; Hanny Lubaba (JOSH: Journal of Sharia, 2026)
Regional autonomy in Lamongan Regency plays a very important role in strengthening local democracy and ensuring that the resulting public policies are responsive to the needs of the community. In this context, the active participation of the community in the policy-making process is the key to achieving the goal of effective and sustainable regional autonomy. Strengthening the capacity of local governments, along with community involvement in decision-making, is indispensable to achieve equitable and sustainable development. The successful implementation of regional autonomy in Lamongan Regency is expected to be a model for other regions in increasing community participation and the quality of public services. Collaboration between local governments and communities not only strengthens regional autonomy, but also supports sustainable development throughout Indonesia. Aspects of transparency and accountability that are improved through effective regional autonomy are important factors in creating good governance. The research methods used in this study include a qualitative descriptive approach to explore the dynamics of community participation and the effectiveness of regional autonomy policies in Lamongan Regency. This study aims to analyze how community participation can increase the effectiveness of regional autonomy policies and support sustainable development in Lamongan Regency. . The efficient application of information technology will strengthen participatory planning practices and encourage community involvement in every stage of development. Therefore, strengthening community capacity through training and socialization of information technology is an important step to achieve more effective and sustainable regional autonomy in Lamongan Regency